PERAN PENDAFTARAN TANAH DALAM MENDORONG PERTUMBUHAN EKONOMI DAN KESEJAHTERAAN MASYARAKAT: KAJIAN PUSTAKA TENTANG EFEKTIVITAS KEBIJAKAN, KETERJANGKAUAN BIAYA DAN KUALITAS LAYANAN ADMINISTRASI PERTANAHAN - Loso Judijanto (CV. ADIBA AISHA AMIRA, 2025)
Land registration plays a strategic role in promoting economic growth and improving community welfare by providing legal certainty regarding land ownership rights. Through programmes such as the Complete Systematic Land Registration (PTSL) programme, the government is seeking to accelerate the process of comprehensive and equitable land certification, which not only strengthens land rights but also opens up access to formal financing and investment opportunities for the community. This literature review examines the effectiveness of land registration policies, focusing on affordability and the quality of land administration services as determining factors for the successful implementation of the programme. The results of the study show that the effectiveness of land registration policies is highly dependent on the ability of the service system to provide fast, transparent, and accessible administrative processes for all levels of society, especially the economically disadvantaged. The affordability of registration is important so that the community is not prevented from obtaining land certificates, while the quality of professional services supported by information technology increases public trust and participation. Synergy between inclusive policies and improvements in the quality of administrative services is important to achieve the goals of increasing economic growth and welfare through land ownership security. In conclusion, land registration is an important instrument in national development that can provide a legal and economic foundation for the creation of higher asset values, broader financial inclusion, and social stability that supports sustainable development. The government needs to continue to evaluate and innovate land administration policies and services so that the benefits of land registration can be optimally and equitably felt by all Indonesians.